Matrine reverses the resistance of Haemophilus parasuis to cefaclor by inhibiting the mutations in penicillin-binding protein genes (ftsI and mrcA) - Zhao, JingChao; Yang, Wen; Deng, Hui; Li, Dong; Wang, QianYong; Yi, LingXian; Kuang, QiHong; Xu, Rui; Li, Di; Li, RuoNan; Yu, DaoJin; Yang, Bo (Frontiers in Microbiology, 2024)
To explore an effective strategy to address the challenge of β-lactams resistance in Haemophilus parasuis (H. parasuis), we screened one cefaclor (CEC)-resistant strain (clinical strain C7) from eight clinical H. parasuis strains and determined the underlying resistance mechanism. Then, we investigated the reversal effect of matrine (MT) on the resistance of this strain to CEC. The results showed that (i) the production of β-lactamase, overexpression of AcrAB-TolC system, and formation of biofilm might not be responsible for the resistance of clinical strain C7 to CEC; (ii) fourteen mutation sites were found in four PBP genes (ftsI, pbp1B, mrcA, and prcS) of clinical strain C7, among which the mutation sites located in ftsI (Y103D and L517R) and mrcA (A639V) genes triggered the resistance to CEC; (iii) the minimum inhibitory concentration (MIC) of CEC against clinical strain C7 was reduced by two to eight folds after MT treatment, accompanied by the significant down-regulated expression of mutated ftsI and mrcA genes. Based on such results, we believed that MT could reverse the resistance of H. parasuis to CEC by inhibiting the mutations in ftsI and mrcA genes. Our research would provide useful information for restoring the antimicrobial activity of β-lactams and improving the therapeutic efficacy of Glässer’s disease.